2013
DOI: 10.1128/jcm.02966-12
|View full text |Cite
|
Sign up to set email alerts
|

Region of Difference 4 in Alpine Mycobacterium caprae Isolates Indicates Three Variants

Abstract: The lack of complete genome sequence information for Mycobacterium caprae complicates a robust differentiation of M. caprae and Mycobacterium bovis. In this study, the presence or absence of M. caprae-specific single nucleotide polymorphisms in lepA and gyrB genes was assessed. The region of difference 4 (RD4) was analyzed for the identification and characterization of M. caprae. Molecular characteristics were evaluated in 12 recent M. caprae isolates from livestock and wildlife collected over a 3-year period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 39 publications
1
43
1
1
Order By: Relevance
“…Based on the distribution of the region of difference 9 (RD9) and the M. tuberculosis deleted region TbD1, three main lineages were defined (57). The lineage deleted for RD9 comprises M. africanum, prevalent in humans in West Africa, as well as a range of subspecies with animal reservoirs, such as Mycobacterium microti, a pathogen originally isolated from voles that also infects cats (61) and sporadically humans (62), Mycobacterium pinnipedii, which was isolated from fur seals and sea lions in different continents (63), Mycobacterium caprae, isolated from goats and deer (64,65), and M. bovis, the bovine tubercle bacillus, which can infect a wide range of wild and domestic animals (66). The spectrum of RD9-deleted tubercle bacilli was further enriched by the identification of Mycobacterium mungi (67), the dassie bacillus (68, 69), a chimpanzee isolate (70), and Mycobacterium orygis, which is found in antelopes but was also repeatedly isolated from human tuberculosis cases (40).…”
Section: Microevolutionary Genomics Of the Tubercle Bacillimentioning
confidence: 99%
“…Based on the distribution of the region of difference 9 (RD9) and the M. tuberculosis deleted region TbD1, three main lineages were defined (57). The lineage deleted for RD9 comprises M. africanum, prevalent in humans in West Africa, as well as a range of subspecies with animal reservoirs, such as Mycobacterium microti, a pathogen originally isolated from voles that also infects cats (61) and sporadically humans (62), Mycobacterium pinnipedii, which was isolated from fur seals and sea lions in different continents (63), Mycobacterium caprae, isolated from goats and deer (64,65), and M. bovis, the bovine tubercle bacillus, which can infect a wide range of wild and domestic animals (66). The spectrum of RD9-deleted tubercle bacilli was further enriched by the identification of Mycobacterium mungi (67), the dassie bacillus (68, 69), a chimpanzee isolate (70), and Mycobacterium orygis, which is found in antelopes but was also repeatedly isolated from human tuberculosis cases (40).…”
Section: Microevolutionary Genomics Of the Tubercle Bacillimentioning
confidence: 99%
“…In our approach using the SybrGreenPCR and melting curve analysis as described by Pinsky and Banaei (14), we identified 79 isolates with RD4-and 7 isolates with RD4+. During our research Domogalla et al (15) reported diversity in the RD4 in alpine M. caprae isolates and found three variants of the isolates: Allgau type (conserved RD4), Karwendel type (deletion of 5kb) and Lechtal type (deleted RD4). These variants were also confirmed in Bavarian and Austrian cattle and wildlife (red deer and fox) (31).…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify whether the RD4-isolates were all M. bovis or the Macedonian M. caprae isolates have deleted RD4, all of the RD4-isolates were subjected to the protocol for detection of M. caprae specific SNPs in the lepA gene (15,16). From the 79 (RD4-) isolates, 8 isolates were identified as M. caprae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…fordul elő a környezetünkben, de a Mycobacterium tuberculosis komplex tagjai között található a legtöbb aerob, obligát patogén (Brites et al, 2015;Domogalla et al, 2013;Donoghue, 2008;Holloway et al, 2011;Mándi, 2013;. Az aktív tüdő-tbc talaján a megbetegedettek 3-5%-nál fejlődhet ki csonttuberkulózis, amely látható nyomot hagy a csontokon is.…”
Section: Czigler Győző áLtal Tervezett Erzsébet Királyné Szanatórium unclassified